Administração da implementação dos recursos de informática - Meirelles, Fernando de Souza (1990)
The thesis identifies the cssential dimensions of inforrnation resourccs implernentation ianagement, creatcs frameworks capturing these dimensions and analyses the multidimensional and ontingcncial process using as an example of IT-Information Technology, the end-user computing by iicrocomputers. In this direction, it identifies and quantifies several indexes for the implementation lanning and control of the proposed method, thru the analysis of actual cases and a specific research. The objective of the thesis is to create and develop frameworks from the knowledge, reflecting an ralysis of the main existing theories and studies of information resources implementation management. These frameworks are initially deveIoped in the broad context of information resources implementation management, incorporating the particularities of the Brazilian reality, and at the end with an emphases for id-user computing with microcomputers - the IT-Infonnation TechnoIogy or infonnation resource utilized ; an example of the proposition. This proposition is illusrrated, analyzed and confronted with actual cases correspondíng to severa I companies in different stages of the use of the information technology and ianaging the information resourccs also in diverse ways.